Metabolomic Analysis of Two Parmotrema Lichens: P. robustum (Degel.) Hale and P. andinum (Mull. rg.) Hale Using UHPLC-ESI-OT-MS-MS - Torres-Benítez, A.; Rivera-Montalvo, M.; Sepúlveda, B.; Castro, O.N.; Nagles, E.; Simirgiotis, M.J.; García-Beltrán, O.; Areche, C. (MDPI, 2017)
Lichens are symbiotic associations of fungi with microalgae and/or cyanobacteria. Lichens belonging to the Parmeliaceae family comprise 2700 species of lichens, including the Parmotrema genus which is composed of 300 species. The metabolites of this genus include depsides, depsidones, phenolics, polysaccharides, lipids, diphenylethers and dibenzofurans, which are responsible for the biological activities reported including antidiabetic, antihelmintic, anticancer, antioxidant, antibacterial, anti-inflammatory, antimitotic, antitumoral, antifungal, and antioxidant enzyme inhibitory. Due to scarce knowledge of metabolomic profiles of Parmotrema species (P. andinum and P. robustum), a full metabolome study based on ultra-high performance liquid chromatography- diode array detector-electrospray ionization-quadrupole-orbitrap-mass-spectrometry (UHPLC-DAD-ESI-Q-orbitrap MS) was performed for a comprehensive characterization of their substances. From the methanolic extracts of these species, a total of 54 metabolites were identified for the first time using this hyphenated technique, including thirty compounds in P. andinum, and thirty-seven in P. robustum. Moreover, two compounds were not identified as known compounds, and could be new structures, according to our data. This report shows that this technique is effective and accurate for rapid chemical identification of lichen substances and the compounds identified could serve as chemotaxonomic markers to differentiate these ruffle lichens.
Keywords: Parmeliaceae; Lichen; Metabolomics; Orbitrap; Chemistry; Metabolome; Electrospray ionization; Chromatography; Botany; Mass spectrometry; Biology; Biochemistry; Ascomycota; https://purl.org/pe-repo/ocde/ford#1.06.10